Phương pháp xác định mực nước dâng cực đại có thể xảy ra do bão tại khu vực công trình đê biển. - Nguyễn, Văn Lai (Trường Đại học Thủy Lợi, 2020)
Storm surges often happen in short time, but may have great affects on coastal areas. High waves combines with high surge levels can cause significant failures to sea dikes due to wave overtopping and/or even crest overflows. Therefore, the determination of the possible maximum storm surge level is necessary for sea dike design. The envelop of maximum storm surge levels can be determined from numerical model simulations. The lowering of water level in a typhoon may also have affect on the lower part of a dike. The numerical model can provide also this result for stability consideration of the outer slope and bottom protection for sea dikes.